The Influence Of Leadership And Motivation On Work Engagement With Competence As Variable Intervening (Case Study Of Gurusma N 2 Lahat) - M. Satria; Hardiyansyah Hardiyansyah; Nisma Aprini (Penerbit Jurnal Indonesia, 2023)
This study aims to reveal the effect of leadership and motivation on work engagement with competence as an intervention variable (a case study of a teacher at SMA Negeri 2 Lahat). This research method uses a quantitative approach. The research respondents were honorary teachers at SMA Negeri 2 Lahat as many as 39 people. Collecting data using a questionnaire on honorary teachers at SMA Negeri 2 Lahat. The results of the study showed that leadership has a significant effect on honorary teachers' work engagement at SMA Negeri 2 Lahat. Motivation has a significant influence on the work engagement of honorary teachers at SMA Negeri 2 Lahat. Competence has a significant influence on honorary teachers' work engagement at SMA Negeri 2 Lahat. Leadership, Motivation, and Competence have a significant influence jointly on honorary teachers' Work Engagement at SMA Negeri 2 Lahat.